Growing into it:evidence of an ontogenetic shift in grey whale use of foraging tactics - Bird, Clara; Pirotta, Enrico; New, Leslie; Bierlich, KC; Donnelly, Marc; Hildebrand, Lisa; Fernandez Ajó, Alejandro; Torres, Leigh (Animal Behaviour, 2024)
Individual specialization may occur relative to diet, behaviour or spatial distribution, potentially leading to differential resource and space use within a population. While specializations have been documented across many animal populations, the underlaying causes of individual specialization (e.g. morphology, age or sex) are not always identified. Causes of specialization can be especially challenging to uncover for large, long-lived marine animals. We used a Bayesian multilevel, multinomial logistic regression model to study the relationships between grey whale, Eschrichtius robustus , use of foraging tactics and morphology (body length and condition), while accounting for habitat characteristics and individual variation in tactic use. The model was informed by a 7-year longitudinal data set of concurrent morphology and foraging behaviour collected using drones. We found evidence of an ontogenetic shift in the use of foraging tactics associated with body length (a proxy for age). Individual specialization in behaviour was also associated with water depth and habitat. After accounting for the effects of these covariates, there was some residual individual level variation in the use of different foraging tactics. Our findings demonstrate variation in resource and habitat use within a baleen whale population at the individual level relative to body length and habitat, suggesting that individual spatial distribution and access to prey may vary by age class. Our results can be applied to investigate whether juveniles and adults differ in their foraging success and resilience to stressors.